Inspiration from Mohd Akmals successful PhD story - Nor Salwana, Mohammad Idris (2021)
KUANTAN, 28 September 2021 - Sharing pictures in the WhatsApp group to share the joy of completing his study was a surprise when his story started to spread on social media a few days ago.